(untitled) (Research, Society and Development, 2022)
This article aims to describe the methodology employed in the 3 data collections of the Santa Maria Adolescent Cohort. The sample was selected from a double stage conglomerate. In all, 1134 adolescents between 11 and 12 years old were evaluated. The second follow-up took place in 2014 and the third in 2018. Clinical baseline variables were collected through oral examinations. The index of lost and filled decayed teeth (DMFT) was used. Demographic and socioeconomic characteristics were collected through questionnaires. Descriptive analysis was performed and the chi-square test was used to assess differences between participants and non-participants. The initial sample had a predominance of females, whites and parents with education greater than or equal to 8 years of schooling. Most had a household income greater than or equal to a minimum wage and a DMFT of 1.15. In 2014, 770 adolescents were reviewed, with a mean age of 14 years, whose predominant characteristics were maintained and the DMFT was 1.48. In 2018, 769 adolescents with an average age of 17.5 years were reviewed. The predominant paternal and maternal education was less than 8 years of schooling and most had a family income below one minimum wage. Comparing participants with non-participants in the three surveys, there was no statistical difference. Longitudinal studies are important to assess the oral condition and its impact on various health outcomes throughout adolescence.